Teufelsbuhlschaft in frühneuzeitlichen Hexenverhörprotokollen aus Grünberg in Niederschlesien = Pakt z diabłem w nowożytnych protokołach z przesłuchań osób posądzanych o czary w mieście Grünberg na Dolnym Śląsku = Pact with the Devil in the early modern witchcraft trial records from Grünberg in Lower Silesia - Dąbrowska-Burkhardt, Jarochna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this paper is a systematic linguistic analysis of lexicological and onomasiological aspects of the semantic field of the lexeme "Devil". The study is a linguistic and historical investigation of a stereotypical structure of statements about "Devil", as found in the examined 17th-century trial protocols from Grünberg in Lower Silesia.
Keywords: protokół; pakt z diabłem; leksyka; onomazjologia; diabeł; Zielona Góra; Grünberg; Dolny Śląsk; 17 w.; witchcraft trial records; pact; devil